The Development of an Interactive Health Education Model Based on the Djuwita Application for Adolescent Girls. (30th November 2017) - Djuwitaningsih, Sri; Setyowati
ABSTRACT: Alarming incidents of maternal deaths in Indonesia are due to three major causes: bleeding, sepsis, and hypertension, in addition to other non-obstetric causes and unsafe abortions. Adolescent girls contributed to maternal mortality based on early marriage, unwanted pregnancy, and childbirth. Prevention efforts have been taken through government programs and non-governmental organizations, but in practice those were considered ineffective. Thus, a preventative effort in the form of health education should be made, preferably embedded in a popular mobile application that most teenagers would be apt to use. This study aimed to develop an interactive health education model based on adolescent-friendly applications, according to their needs. The design of this research was mixed-method. A quantitative approach was used by conducting a survey of 188 teenagers aged 15–19 years in Bogor, West Java, Indonesia through questionnaires. This research also contained a qualitative component via in-depth interviews with students, parents, and counseling teachers. The quantitative results showed that respondents' knowledge was low about male and female reproductive organs, prevention of pregnancy, and the use of condoms. Respondents' attitudes toward risky behaviors indicate a positive attitude about smoking, drinking, and illegal drugs, as well as premarital sex, while respondents have a negative attitude toward unwanted pregnancies. Respondents' attitudes toward application-based health education shows a high interest. Respondents desired that the application have privacy, up-to-date information, interesting features, can be discussed with peer groups and health workers, include a game, animation, and simulation, and can identify reproductive health independently. Qualitative results indicate the need for reliable, accessible, and personal sources of information. The next research recommendation is to develop an interactive health education model based on the application of Djuwita and evaluate its influence on the knowledge, attitudes, and self-efficacy of young women in maintaining their reproductive health.